2021
DOI: 10.3390/microorganisms9020339
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Can Inhibit SARS-CoV-2 In Vitro

Abstract: An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) resulted in the coronavirus disease pandemic, drastically affecting global health and economy. Though the understanding of the disease has improved, fighting the virus remains challenging. One of the strategies is repurposing existing drugs as inhibitors of SARS-CoV-2. Fluoxetine (FLX), a selective serotonin reuptake inhibitor, reportedly inhibits the replication of RNA viruses, especially Coxsackieviruses B (CVB), such as CV-B4 in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 42 publications
(52 reference statements)
4
40
0
Order By: Relevance
“…As mechanisms, the authors describe a lack of acidification in acidic organelles and a change in cholesterol abundance. The observation of the antiviral activity of fluoxetine was also confirmed in other preclinical studies [ 60 , 61 ]. Taken together, these results show the potentially crucial importance of the ASM/ceramide system as a treatment target in COVID-19, a mechanism likely to be shared by all virus variants [ 62 ].…”
Section: The Asm/ceramide System and Sars-cov-2supporting
confidence: 73%
“…As mechanisms, the authors describe a lack of acidification in acidic organelles and a change in cholesterol abundance. The observation of the antiviral activity of fluoxetine was also confirmed in other preclinical studies [ 60 , 61 ]. Taken together, these results show the potentially crucial importance of the ASM/ceramide system as a treatment target in COVID-19, a mechanism likely to be shared by all virus variants [ 62 ].…”
Section: The Asm/ceramide System and Sars-cov-2supporting
confidence: 73%
“…In addition, several repurposed drugs have been introduced which are able to prevent viral entry via different mechanisms. These repurposed drugs, including fluoxetine and itraconazole, which can dysregulate the endosomal cholesterol release and increase endolysosomal cholesterol storage have been suggested as synergistic combinatory therapeutic agents alongside with conventional antiviral therapies (Creeden et al, 2021;Dechaumes et al, 2021;Schloer et al, 2021). According to these promising results, using repurposed therapeutic agents as adjuvant therapy alongside with the two-step strategy seems to be very helpful with comprehensive blockade of viral entry.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Schloer et al (2020) and Zimniak et al (2021) showed the efficacy of these host-directed drugs in fighting COVID-19 infection both alone and in combination with an antiviral drug, remdesivir. In another study, they investigated the in vitro antiviral activity of fluoxetine against SARS-CoV-2 in a model of acute infection and the level of infectious particles was lower than that in controls (Dechaumes et al, 2021). The mechanism through which fluoxetine exhibits its inhibitory effect in viral cell entry is that it prevents endolysosomal acidification by inactivating endolysosomal proton pump (v-ATPase) which leads to endolysosomal pH neutralization.…”
Section: Supporting Evidences For Strategy Cell Entry Mechanism Of Sars-cov-2mentioning
confidence: 99%
“…The HEp-2 cell line (BioWhittaker, Verviers, Belgium) was cultured in Eagle’s Minimum Essential Medium supplemented with 10% FCS, 100 U/mL penicillin and 100 μg/mL streptomycin, and 1% L-glutamine. The diabetogenic strain CV-B4 E2 was provided by Ji-Won Yoon (Julia McFarlane Diabetes Research Center, Calgary, AB, Canada) and was propagated in HEp-2 cells as previously described [ 33 , 36 ]. The viral titers in supernatants were assessed on HEp-2 cell monolayers using the end-point dilution assay.…”
Section: Methodsmentioning
confidence: 99%